Dystocia Due to Incomplete Cervical Dilatation and Breech Presentation of Fetus in a Goat - Sharma, Renu; Gupta, Shashikant; Das, Goutam Kumar; Ghosh , Subrata Kumar (The Indian Journal of Animal Reproduction, 2025)
In the Referral Veterinary Polyclinic, ICAR-Indian Veterinary Research Institute, Bareilly, a case report of a pregnant  doe aged 2 years old who was unable to deliver the fetus was presented. Due to insufficient cervical dilation, doe was  unable to deliver the fetus, resulting in dystocia. Induction treatment was done along with CMC massaging of cervix for  10 minutes after every 30 minutes. After 2 hours of this therapy the cervix was fully dilated and the appearance of water  bags was observed. Then per vaginal examination was done and fetus were observed in posterior presentation which were  delivered by traction. Both live fetuses were having myxoedema and one fetus was without hairs which is characteristic  of congenital goiter in kids. This case report describes an instance of dystocia in a goat caused by ICD and due to breech  presentation of fetuses. The fetuses were delivered successfully.
Keywords: Doe; Dystocia; Myxoedema; Goiter; Breech Presentation